Investigation of Influence Heat Treatment on Mechanical Properties of Welded Joints (مجلة العلوم الشاملة, 2025)
This research investigates the impact of post-weld heat treatment (PWHT) on themechanical properties of butt- welded low carbon steel joints. Welding processes caninduce thermal stresses and microstructural changes that negatively affect mechanicalperformance. The study utilized Shielded Metal Arc Welding (SMAW) with controlledparameters and an E10-60 electrode. Non-destructive testing (NDT) methods, includingDye Penetrant Testing, UV Inspection, and Magnetic Field Detection, were applied toassess weld quality before and after welding. Subsequent heat treatment, specificallytempering at 550°C for 20 minutes followed by slow air cooling, was performed tobalance hardness and toughness. Microstructural analysis and microhardness testingwere conducted to evaluate the effects of the heat treatment on the welded joints. Theresults indicate that tempering significantly reduces hardness, particularly in the HeatAffected Zone (HAZ), and enhances toughness and ductility, which are crucial forpreventing cracking and failure in welded joints.